Implementasi MBKM pada Mahasiswa Program Studi Teknik Elektro Universitas PGRI Madiun - Irna Tri Yuniahastuti; Dody Susilo; Ridam Dwi Laksono; Habi Angga Tristian (Jurnal Paedagogy, 2022)
This study aims to analyze the impact of MBKM, especially the Independent Student Exchange of Electrical Engineering study program at UNIPMA. In this study, the implementation of MBKM was tested in the Electrical Engineering study program, especially the electrical power installation course. This research method used a descriptive method with a quantitative approach. The subjects of this research were third-semester students in the Electrical Engineering study program of UNIPMA. This research used observation, interviews, and documentation to collect the data. The class was divided into three groups, each consisting of four students. Group I consisted of Independent Student Exchange (ISE) students, and group II and III consisted of regular groups. The result of this study showed that the average score for group I was higher than the others. Followed by statistical tests, group I had a significant effect on group II and group I had no significant impact on group III. In brief, MBKM has a positive learning impact on electrical power installation courses.